Bio-psychosocial Determinants of Quality of Life in the Elderly - Roh Hastuti Prasetyaningsih; Dono Indarto; Muhammad Akhyar (Journal of Epidemiology and Public Health, 2016)
Background: The quality of life of elderly people has become relevant with the demographic shift that has resulted in greying of population. In Indonesia the number of old people has been increasing rapidly. Despite longer life span, this situation poses quality of life concern. It is then of interest to study determinants of quality of life in the elderly, so that necessary measures can be taken to improve the quality of life in the elderly. This study aimed to examined bio-psichosocial factors associated with the quality of life in the elderly.Subjects and Method: This was an analytic observational study using case control design. This study was conducted in Laweyan and Banjarsari, Surakarta. A total of 141 elderly consisting of 47 elderly who lived in the nursing home and 94 elderly who lived at their own home, were selected for this study, by fixed exposure sampling. The independent variables were age, education, income, family support, residential status, and depression. The dependent variables was quality of life. The data were collected with a set of questionnaire and analyzed using path analysis model.Results: As many as 40.4% of the elderly studied had good quality of life. Higher income (b = 0.93; 95%CI = 0.06 to 1.86; p = 0.048) and education (b=0.82; 95%CI= -0.01 to 1.66; p= 0.053) is associated with better quality of life. Depression (b =-1.01; 95%CI =-1.78 to -0.23; p = 0.010) and age ≥ 60 years old (b=-0.47; 95% CI= -1.28 to 0.33; p= 0.249). Living at own home decreased depression, higher education increased income, family support increased living at home.Conclusion: Income and education increase the quality of life. Depression and older age decrease the quality of life.Key words: bio-psychosocial, quality of life, elderlyCorrespondence: Roh hastuti Prasetyaningsih. Health Polytechnics, Poltekkes Surakarta, Central JavaJournal of Epidemiology and Public Health (2016), 1(2): 108-117https://doi.org/10.26911/jepublichealth.2016.01.02.04